2022
DOI: 10.1007/jhep12(2022)147
|View full text |Cite
|
Sign up to set email alerts
|

Manifestly SL(2, R) Duality-Symmetric Forms in ModMax Theory

Abstract: In this paper, we will investigate a manifestly SL(2, R)-invariant structure for the energy-momentum tensor of ModMax theory as a nonlinear modification of Maxwell electrodynamics which includes conformal invariance as well. In the context of this theory, we show that the energy-momentum tensor of the generalized Born-Infeld theory can also be written in the same invariant form. We will find manifestly duality-invariant parts of the actions corresponding to the invariant couplings λ and γ in these theories. It… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…The deformation of the ModMax theory, under T T -like flows is investigeted in [25] and it is shown that the deformed theory is the generalized BI NLE. Also, in [26], a manifestly SL(2, R)-invariant form for the energymomentum tensor of ModMax theory, is investigated. The asymptotically AdS accelerated black holes in ModMax theory and their thermodynamics is studied in [27].…”
Section: Introductionmentioning
confidence: 99%
“…The deformation of the ModMax theory, under T T -like flows is investigeted in [25] and it is shown that the deformed theory is the generalized BI NLE. Also, in [26], a manifestly SL(2, R)-invariant form for the energymomentum tensor of ModMax theory, is investigated. The asymptotically AdS accelerated black holes in ModMax theory and their thermodynamics is studied in [27].…”
Section: Introductionmentioning
confidence: 99%
“…These subtleties are important for the 3d stress tensor flows for scalar theories considered in[32] 5. Although we have made no additional assumptions about the field content of the theory L λ , or any additional symmetries such as electric-magnetic duality invariance, we note that a relation of the form (25) can be derived via different means in the context of 4d duality-invariant electrodynamics[59,60].…”
mentioning
confidence: 99%